PRINCIPLE OF RANKING MAKING OF MULTI-PROJECTION DECISION - Olga N. Lapaeva (Статистика и экономика, 2016)
The principle of ranking making of multi-projection decision in economics is setforth in the article. The principle envisagesﬁ nding of ﬁrst and surrounding ranks ineach projection and result making bycrossing of partial sets.